A unified approach to measuring u* - Richard K. Crump; Stefano Eusepi; Marc Paolo Giannoni; Ayşegül Şahin (Federal Reserve Bank of New York, 2019)
This paper bridges the gap between two popular approaches to estimating the natural rate of unemployment, u*. The first approach uses detailed labor market indicators, such as labor market flows, cross-sectional data on unemployment and vacancies, or various measures of demographic changes. The second approach, which employs reduced-form models and DSGE models, relies on aggregate price and wage Phillips curve relationships. We combine the key features of these two approaches to estimate the natural rate of unemployment in the United States using both data on labor market flows and a forward-looking Phillips curve that links inflation to current and expected deviations of unemployment from its unobserved natural rate. We estimate that the natural rate of unemployment was around 4.0 percent toward the end of 2018 and that the unemployment gap was roughly closed. Identification of a secular downward trend in the unemployment rate, driven solely by the inflow rate, facilitates the estimation of u*. We identify the increase in labor force attachment of women, decline in job destruction and reallocation intensity, and dual aging of workers and firms as the main drivers of the secular downward trend in the inflow rate.
Keywords: D22; E24; J11; 330; firm dynamics; demographics; business dynamism; macroeconomics